Akumulasi Prolin dan Indeks Toleransi Kalus Padi yang Diseleksi Polietilen Glikol (PEG) Secara In Vitro Sebagai Marka Toleransi Kekeringan - Juswardi Juswardi; Nina Tanzerina (Jurnal Penelitian Sains, 2003)
Proline accumulation and tolerance index in rice callus by in vitro selected on polyethylene glycol (PEG) as drought tolerance marker. The strait improvement of rice by in vitro has been done with selected callus rice on polyethylene glycol (PEG 6000). The research conducted to known proline accumulation and tollerance index in callus that selected by in vitro on PEG as tolerance index marker. Callus inducted from endosperm of cultivars Rojolele rice on MS medium with 10-5M 2,4-D. The selection of callus sub cultured step by step with add of PEG 250, 500 and 750 ppm on MS medium. Design of experiment used completely randomise design with two treatments that are selected callus and non selected calus and 10 replications. The observed on callus weight and proline content. Data analysed by t test for proline content and tolerance index for callus weight. The result shown that non significant differ on proline content if compare selected callus to non selected callus respectively 105,12% and 100%. Tolerance index of selected callus not differ from non-selected callus. Proline accumulation and tolerance index not yet guarantee as tolerance marker to  drought stress.